Exosomes of Human Umbilical Cord MSCs Protect Against Hypoxia/Reoxygenation-Induced Pyroptosis of Cardiomyocytes via the miRNA-100-5p/FOXO3/NLRP3 Pathway - Liang, Chenyu; Liu, Yang; Xu, Huifeng; Huang, Junling; Shen, Yi; Chen, Faxiu; Luo, Ming (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Acute myocardial infarction (AMI) is one of the leading causes of morbidity and death worldwide. Studies indicated that microRNAs in mesenchymal stem cells (MSCs) derived exosomes are crucial for treating many diseases. Methods: Human umbilical cord MSC (hucMSC) were isolated and hucMSC derived exosomes (hucMSC-exo) were isolated and used to treat cardiomyocytes underwent hypoxia/reoxygenation (H/R) challenge. Bioluminescence assessment was used to study binding of miRNA to its targeting gene. Results: We found that H/R decreased viability of AC16 cells and increased NLRP3 expression, and both were abolished by administration of hucMSC-exo. Administration of exosomes from negative scramble miRNA (NC)-transfected hucMSC blocked H/R-caused LDH release, pyroptosis, over-regulation of NLRP3, activated caspase-1(p20) and GSDMD-N, as well as release of IL-1β and IL-18. More importantly, in comparison to exsomes from NC-transfected hucMSC, exsomes from miR-100-5p-overexpressing hucMSC had more obvious effects, while those from miR-100-5p-inhibitor-transfected hucMSC showed less effects. Functional study showed that miR-100-5p bound to the promoter region of FOXO3 to suppress its transcription. Moreover, overexpression of FOXO3 abolished the protective effects of miR-100-5p. Conclusions: Enriched miR-100-5p in hucMSC-exo suppressed FOXO3 expression to inhibit NLRP3 inflammasome activation and suppress cytokine release, therefore protected cardiomyocytes from H/R-induced injury.